Social Media Fiqh: A Study of Religious Moderation - Muhammad Torieq Abdillah; Sulaiman Kurdi (Majalah Ilmu Pengetahuan dan Pemikiran Keagamaan Tajdid, 2022)
This study examines the phenomenon of social media in Indonesia by looking at the existing limits. The limitation in question is the existence of social media fiqh from the perspective of religious moderation. Social media fiqh is at least present to be a sign of the negative issues and trends that exist in social media. The research method used is a qualitative descriptive literature study. The theory used is the theory of religious moderation analysis. The results showed that the social media phenomenon in Indonesia found a lot of freedom that leads to cyberbullying, intolerance, radicalism, and others. In addition, quite often, the occurrence of hoaxes scattered on social media is the cause of extremist ideas that make a clash in socio-religious in Indonesia. Religious moderation is present in limiting people's behavior to maintain harmony. These restrictions also cannot be separated from the messages in the Qur'an and Hadith so that activities on social media are controlled. Then, this step supports the issue of religious moderation echoed by the government through the Ministry of Religious Affairs. Therefore, the creation of social media fiqh is worth religious moderation. However, it is also necessary to know the characteristics of religious moderation to be applied in social media, such as tawassuth (taking the middle way), tasamuh (tolerance), musawah (egalitarian or equality), and tahadhdhur (civility). Social media fiqh became the answer to limit people's behavior on social media by linking it with religious moderation as an answer to social change on social media